Magnetic resonance microscopy of trabecular bone - Cova, Maria (Radiology and oncology (Ljubljana), 2002)
Background. Bone diseases such as osteoporosis lead to changes in the trabecular bone mass and architecture. Improved methods for the quantitative assessment of trabecular bone are needed to better understand the role of trabecular architecture in bone strength. MR microscopy (MRM),'with its ability to achieve resolutions below 50 micromol has proved to be particularlyuseful for the ex vivo evaluation of the complex archi- tecture oftrabecular bone. In this study, we describe the use of projection reconstruction (PR) with MRM for the quantitative evaluation of the three-dimensional structure of trabecular bone explants and for the predictionof their biomechanical properties. Material and methods. High-resolution 3D PR and trabecular bone explants were analysed to determine standard morphologic parameters such as trabecular bone volume fraction (BV/TVor Vv), trabecular thick- ness (Tb.Th) and trabecular separation (Tb.Sp). Segmentation of the high-resolution images into bone and bone marrow was obtained by using a Bayesian approach. The derived parameters were finallyincluded in non-linear mathematical models for the prediction of Young's modulus (YM). Results. The parameters derived from the PR spin-echo were found to be stronger predictor of YM (RZ = 0.86) than those derived from the conventional spinecho images (R2 = 0.75) used for comparison. Conclusions.This ex vivo approach should be readily adaptable to the studies in human subjects.
Keywords: bolezni kosti; Bone And Bones; Bone Diseases; diagnostika; Kost, bolezni; Kosti; Magnetic Resonance Imaging; Magnetna resonanca slikovna; osteoporoza; radiološka diagnostika; slikanje z jedrsko magnetno resonanco; Ultrastructure